1992
DOI: 10.1111/j.1744-6570.1992.tb00855.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential Versus Actual Faking of a Biodata Form: An Analysis Along Several Dimensions of Item Type

Abstract: Two studies examined faking of a 25‐item biodata questionnaire. The first study investigated potential and actual faking of the form using three groups: a group told to make themselves look as good as possible, a group told to complete the form honestly, and a group completing the instrument in a real selection situation. Subjects were 58 current employees and 231 job applicants. Results indicated that subjects could fake the instrument when instructed to do so. Also, some faking appeared to be occurring in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 22 publications
1
43
0
Order By: Relevance
“…Moreover, Atwater (1980) found that verifiable items were less prone to distortion compared with nonverifiable items. By using a sample of 58 current employees and 231 job applicants, Becker and Colquitt (1992) also found that biodata items that are faked in practice tend to be less historical, objective, discrete, verifiable, and more job relevant.…”
Section: Structured Interviewsmentioning
confidence: 99%
“…Moreover, Atwater (1980) found that verifiable items were less prone to distortion compared with nonverifiable items. By using a sample of 58 current employees and 231 job applicants, Becker and Colquitt (1992) also found that biodata items that are faked in practice tend to be less historical, objective, discrete, verifiable, and more job relevant.…”
Section: Structured Interviewsmentioning
confidence: 99%
“…Faking has been extensively studied in non-cognitive self-report measures such as personality inventories, biodata inventories, and integrity tests (e.g., Alliger & Dwight, 2000;Becker & Colquitt, 1992;Dalen, Stanton, & Roberts, 2001;Graham, McDaniel, Douglas, & Snell, 2002;Kluger & Collela, 1993;McFarland, Ryan, & Ellis, 2002;Ones, Viswesvaran, & Reiss, 1996;Ones & Viswesvaran, 1998).…”
Section: Response Distortion and Sjtsmentioning
confidence: 99%
“…A second group of methods is more proactive as they aim to prevent faking. One approach has consisted of using warnings that fakers can be identified and will be penalized (Becker & Colquitt, 1992;Dwight & Donovan, 2003;Pace & Borman, 2006;Vasilopoulos, Cucina, Dyomina, Morewitz, & Reilly, 2006). So far, the empirical evidence showed only meager effects [around .25 standard deviations (SDs)] for a combination of identification-only and consequences-only warnings on predictor scores and faking scale scores (Dwight & Donovan, 2003).…”
Section: Overview Of Approaches To Detect or Control Fakingmentioning
confidence: 99%
“…Finally, constative theorists have suggested that item responses are more likely to correspond to someone's actual personality if the item refers to objective, verifiable facts. In the industrial-organizational literature (e.g., Becker & Colquitt, 1992), biographical items (e.g., "My high school grade point average was higher than 3.00") have been highly touted because such items are more verifiable than items that require subjective interpretation (e.g., "I did well in school"). Goldberg (1963) reported that people respond more consistently to items that reflect observable behavior than items reflecting attitudes, values, or other internal states of mind.…”
Section: The Constative View Of Personality Item Responsesmentioning
confidence: 99%